THE EFFECT OF PROJECT-BASED LEARNING (PJBL) MODEL WITH PADLET APPLICATION ON CRITICAL THINKING SKILLS OF CLASS XI STUDENTS IN HISTORY SUBJECTS AT SMAN 22 EAST JAKARTA: Pengaruh Model Project Based Learning (PjBL) Dengan Aplikasi Padlet Terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas XI Pada Mata Pelajaran Sejarah di SMAN 22 Jakarta Timur - Sofyan Wijaya; Agus Rustamana; Yuni Maryuni (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study aims to analyse the effect of applying the project-based learning (PjBL) model with padlet application on students' critical thinking skills in Indonesian history subjects, especially on ethical politics and national movements. This research used quasi-experimental method with nonequivalent control group design and non-probability sampling technique through purposive sampling. The research subjects consisted of class XI F-I as the experimental group and class XI F-VII as the control group at SMAN 22 East Jakarta, with each group totalling 33 students. The research instrument was a 10-item description test used to measure students' critical thinking skills. The data were analysed using two-party t-test with pooled variance formula, which was conducted with the help of Microsoft Excel 2016 software. The analysis results showed that the tcount value (2.32) ≥ ttable (2.00) at the significance level α = 0.05, so the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Based on the results of the study, it can be concluded that the application of the project-based learning (PjBL) model with padlet has a significant effect on improving students' critical thinking skills. Therefore, this learning model can be used as an alternative strategy in teaching Indonesian history to develop critical thinking skills more optimally.